Strategi Pengembangan Peternakan Itik Di Distrik Semangga Kabupaten Merauke - Maya Novi (Universitas Musamus, Merauke, Papua, 2019)
Semangga District is a very potential area for the development of duck farming because most of the area consists of paddy fields. This study aims to identify the potential development of duck farming and analyze alternative strategies for developing duck farms in the Semangga District. This study used qualitative research methods. Data collection by in-depth interview, observation and document study. Data is processed using a SWOT analysis. The results showed that the Duck Farm System in the Semangga District used a Semi-Intensive System. This can be illustrated through several factors namely housing, nursery, care/maintenance, food, disease control, marriage, and harvesting. Identification of the potential development of duck farming includes internal factors and external factors. Alternative strategies that can be carried out for the development of duck farming in the Semangga District are to collaborate with related agencies to improve knowledge and technology in business development, expand business land by utilizing the support provided, form breeder groups, provide knowledge of feed technology, provide information / training for breeders, utilize capital assistance to develop businesses, evaluate and improve business management and foster or cooperate with other institutions to develop businesses.